Patterns of hybridization among cutthroat trout and rainbow trout in northern Rocky Mountain streams. Issue 3 (11th January 2016) - McKelvey, Kevin S.; Young, Michael K.; Wilcox, Taylor M.; Bingham, Daniel M.; Pilgrim, Kristine L.; Schwartz, Michael K.
Abstract: Introgressive hybridization between native and introduced species is a growing conservation concern. For native cutthroat trout and introduced rainbow trout in western North America, this process is thought to lead to the formation of hybrid swarms and the loss of monophyletic evolutionary lineages. Previous studies of this phenomenon, however, indicated that hybrid swarms were rare except when native and introduced forms of cutthroat trout co‐occurred. We used a panel of 86 diagnostic, single nucleotide polymorphisms to evaluate the genetic composition of 3865 fish captured in 188 locations on 129 streams distributed across western Montana and northern Idaho. Although introgression was common and only 37% of the sites were occupied solely by parental westslope cutthroat trout, levels of hybridization were generally low. Of the 188 sites sampled, 73% contained ≤5% rainbow trout alleles and 58% had ≤1% rainbow trout alleles. Overall, 72% of specimens were nonadmixed westslope cutthroat trout, and an additional 3.5% were nonadmixed rainbow trout. Samples from seven sites met our criteria for hybrid swarms, that is, an absence of nonadmixed individuals and a random distribution of alleles within the sample; most (6/7) were associated with introgression by Yellowstone cutthroat trout. In streams with multiple sites, upstream locations exhibited less introgression than downstream locations. We conclude that although the widespread introduction of nonnative trout within the historical range of westslope cutthroat trout has increased the incidence of introgression, sites containing nonadmixed populations of this taxon are common and broadly distributed. Abstract : Hybridization between westslope cutthroat trout and Yellowstone cutthroat trout was analyzed using a panel of 86 diagnostic, single nucleotide polymorphisms to evaluate the genetic composition of 3865 fish captured in 188 locations on 129 streams distributed across western Montana and northern Idaho. Nonintrogressed fish dominated the sample. Widespread introduction of nonnative trout within the historical range of westslope cutthroat trout has increased the incidence of introgression, but sites containing nonadmixed populations are common and broadly distributed.